A contemporary look at FVIII inhibitor development: still a great influence on the evolution of hemophilia therapies. Issue 2 (1st February 2018) - Santagostino, Elena; Young, Guy; Carcao, Manuel; Mannucci, Pier Mannuccio; Halimeh, Susan; Austin, Steve
ABSTRACT: Introduction : The development of inhibitors against factor VIII (FVIII) replacement therapy remains the most important challenge for clinicians in the treatment of hemophilia patients. This review focusses on risk factors and management of FVIII inhibitors, particularly in light of SIPPET study findings and subsequent analyses. Areas covered : A brief history and evolution of hemophilia therapies is provided, including an overview of conventional and new (including investigational) therapeutic approaches for the treatment of hemophilia. The SIPPET study, the first randomized clinical trial to demonstrate a lower incidence of inhibitors in previously untreated patients treated with plasma-derived FVIII products compared with recombinant FVIII products, has generated much debate. We review the SIPPET trial and reactions, in addition to preliminary observations from a single center's experience, the cost impact of inhibitors, recent findings from SIPPET subanalyses, and inhibitor development in previously-treated patients. Expert commentary : Despite recent advances in potential new treatment options for hemophilia, conventional factor replacement concentrates currently remain the cornerstone of treatment. It is paramount that clinicians familiarize themselves with the findings from the SIPPET trial and substudies, in order to better inform their patients and families on inhibitor risk factors and to aid the treatment decision-making process.